2014
DOI: 10.1002/2012wr013038
|View full text |Cite
|
Sign up to set email alerts
|

Long-term snow distribution observations in a mountain catchment: Assessing variability, time stability, and the representativeness of an index site

Abstract: 1] This study presents an analysis of snow distribution heterogeneity and the factors affecting this variability. The analysis focuses on manually sampled data from 21 snow surveys covering 11 years at the drift-dominated Reynolds Mountain East catchment (0.36 km 2 ) in southwestern Idaho, USA. Surveys were conducted midwinter and in early spring. Interseason and intraseason trends were examined along with the time stability of distributions, goodness-of-fit to theoretical distributions, and the representative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
84
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 54 publications
8
84
2
Order By: Relevance
“…Also we have shown that its effect evolved during the snow accumulation and melting periods over two years having highly contrasting climatic conditions and snow accumulation amounts Many studies have analyzed the spatial distribution of SD in mountain areas considering both, intra-and inter-annual variability of the topographic control on the snowpack distribution (Anderton et al, 2004;Erickson et al, 2005;López-Moreno et al, 2010;McCreight et al, 2014). Other researches have also focused their attention in long-term interannual snow distribution analyses (Jepsen et al, 2012;Sturm and Wagner, 2010;Winstral and Marks, 2014). The results of these previous works have highlighted the difficulties in fully explaining the distribution of snow in complex mountainous terrain.…”
Section: Discussionmentioning
confidence: 99%
“…Also we have shown that its effect evolved during the snow accumulation and melting periods over two years having highly contrasting climatic conditions and snow accumulation amounts Many studies have analyzed the spatial distribution of SD in mountain areas considering both, intra-and inter-annual variability of the topographic control on the snowpack distribution (Anderton et al, 2004;Erickson et al, 2005;López-Moreno et al, 2010;McCreight et al, 2014). Other researches have also focused their attention in long-term interannual snow distribution analyses (Jepsen et al, 2012;Sturm and Wagner, 2010;Winstral and Marks, 2014). The results of these previous works have highlighted the difficulties in fully explaining the distribution of snow in complex mountainous terrain.…”
Section: Discussionmentioning
confidence: 99%
“…Even though depths can vary greatly over space in a snow pack, the overall distribution of snow has been found to exhibit spatial similarities from year to year (Hiemstra et al, 2006;Sturm and Wagner, 2010;Winstral and Marks, 2014). Repeated lidar surveys throughout single seasons and over multiple seasons (Deems et al, 2008) have found similar results through fractal analyses of the snow depth distributions.…”
Section: A Hedrick Et Al: Lidar Validation Of Snodasmentioning
confidence: 99%
“…Precipitation station data were included based on (1) the degree of wind sheltering due to topography and vegetation and (2) the spatial arrangement of measurement locations. Wind-sheltered precipitation gauges were preferentially used over wind exposed sites following Winstral et al (2013) and Winstral and Marks (2014). However, some exposed precipitation stations were used because they were the only ones representing large portions of RCEW (e.g., 057, 049, and 127).…”
Section: Data Preparation and Spatial Distributionmentioning
confidence: 99%